Historique des normes juridiques dans les pénitenciers au Canada - Lemonde, Lucie (Criminologie, 1995)
The author brings forth three main periods in the evolution of legislative, statutory and administrative norms regarding the powers of the correctional authorities and the treatment of prisoners in Canadian penitentiaries, from 1834 to present. The first two periods are characterized by an extreme prescriptive profusion typical of utilitarian institutions and by the delegation of normative power to administrative authorities. During the 1980's, the intervention of the courts forces the legislature to progressively integrate the notion of respect for the rule of law and for the principles of procedural equity. The new Law on the correctional system and conditional release in effect since November 1992, is radically distinct from the types of legislations that prevailed for the preceeding fifty years in that it incorporates and ratifies the discourse on prisoners' rights. According to the author, the change of perspective is radical: the utilitarian function of carcéral norms has weakened at the benefit of a function protective of prisoners' rights.